Meningkatkan Kesadaran Masyarakat Terhadap Kesehatan Dan Mengedukasi Dalam Ilmu Pengetahuan Umum Dan Pengelolaan Umkm Menuju Kawasan Sehat, Mandiri Dan Religius - Pagala, Ashar (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Sultan Aji Muhammad Idris State Islamic University (UINSI) Samarinda as one of the State Universities in Indonesia is expected to be able to play a role in implementing the values ​​of the Tri Dharma of Higher Education, namely the dharma of education and teaching, the dharma of research and the dharma of community service. LP2M as a research and community service center is responsible for organizing the Field Work Lecture program. On this occasion, we raised the theme